Estudo in-situ de filmes magnéticos ultrafinos por magnetometria Kerr e técnicas de superfície - Gustavo Fóscolo de Moura Gomes (2009)
The aim of this work is to apply Kerr magnetometry to ultra-thinmagnetic films. A Kerr magnetometer operating in ultra high vacuum isdescribed, as well as the modications and optimizations we have done, to achieve atomic monolayer sensibility. We present measurements performed on samples with different magnetic properties, such as exchange bias effect, systems with magnetic anisotropy (determination of hard/soft axis) and others. The in-situ prepared samples were chemically and structurally characterized by means of surface sensitive techniques (XPS, LEED, RHEED, CEMS). In order to include the magneto-optic Kerr eect (MOKE) in the Maxwell equations, one term due to the Lorentz force is added to the electric displacement vector. Consequently, the electric permissivity tensor contains the magneto-optic constant and the relative magnetizations (mx, my and mx), and the magnetic information is included in the coecients of the Fresnel reection matrix. The Kerr intensity is calculated for a series of congurations of the Kerr magnetometer (angles of polarizers, modulator, etc.). To separate the three components of magnetization, we demonstrate that a linear combination of measurements at (at least) two different congurations of the magnetometer, is necessary. We have applied one of the developed methods to the FexCo1-x/Pd(100) system to calculate mz for different stoichiometries (x = 30, 50) and with thermal annealing of the films.